Synergy of collaboration and competitiveness for sustainable handcraft small medium enterprises - Alhidayatullah, Alhidayatullah (Universitas Ahmad Dahlan, 2025)
Purpose-This study seeks to examine the impact of collaborative synergy on business competitiveness and sustainability, and to evaluate the effect of competitiveness on business sustainability within handmade small medium enterprises. This research originates from the issues of inadequate formal collaboration, restricted product competitiveness, and sustainability concerns within the local culture-based creative industry sector. Methodology-The study employs a quantitative methodology via a survey technique. The research population comprises 285 handicraft small medium enterprises registered with the Sukabumi cooperatives and small medium enterprises office in 2024. Data was gathered using a Likert scale questionnaire and processed via structural equation modeling with Smart PLS version 4.0. Findings-The study’s findings indicate that cooperation synergy significantly enhances competitiveness, collaboration synergy significantly improves business sustainability, and competitiveness significantly contributes to business sustainability. Likewise, the synergy of collaboration towards business sustainability mediated by competitiveness has a significant positive effect. This research substantiates that strategic collaboration is the primary catalyst for competitiveness and the cornerstone of small medium enterprises sustainability. Research Limitations-This study is limited to handcraft small medium enterprises in Sukabumi, so the findings cannot be generalized to other sectors or regions. The cross-sectional survey captures only one point in time, restricting analysis of long-term dynamics. Self-reported data may introduce response bias, and external factors such as government policy, economic conditions, and digital transformation were not included in the model.. Novelty-This research is new due to the integration of three critical variables: Cooperation synergy, competitiveness, and company sustainability, inside an empirical model grounded in resource-based view and dynamic capability theory, particularly concerning creative small medium enterprises rooted in local culture.